The Study on Lasing Threshold Properties of Rhodamine B in Glycerol Aqueous Solution - Yuanxian Zhang; Dongyang Li; Yonxiong Ou; Xiaoyun Pu; Yuze Sun (IEEE Photonics Journal, 2019)
An optical fiber is integrated in a polydimethylsiloxane substrate microfluidic channel. The laser gain medium consists of glycerol aqueous solution doped with rhodamine B (RhB) molecules, which has a lower refractive index (RI) than that of the optical fiber. The circular cross section of the optical fiber forms an optofluidic ring resonator and hosts high-quality (Q) whispering gallery modes (WGMs). Optically pumped along the fiber axis, lasing threshold properties of the RhB glycerol aqueous solution have been investigated. With the increase of both RhB dye concentration and the RI of the glycerol aqueous solution, the recorded lasing threshold decreases at first and then increases. Therefore, there is a best dye concentration as well as a best RI of the dye solution that corresponds to the lowest lasing threshold. Additionally, lasing threshold for the mixed solution of ethanol and ethylene glycol doped with RhB molecules is also demonstrated, which is much higher than that of the glycerol aqueous solution for the same dye concentration and the same RI of the dye solution. Based on evanescent wave pumped and gain coupled WGM lasing theory, we compute the lasing threshold varied with the dye concentration and the RI of the dye solution. The simulation results agree well with the experimental data.